IMPLEMENTATION OF ONLINE LEARNING USING GOOGLE SITES IN INCREASING STUDENT’S INTEREST IN LEARNING IN ISLAMIC EDUCATION - Luluk Makrifatul Madhani; Mohamad Joko Susilo (Universitas Islam Indonesia, 2023)
The current Covid-19 pandemic has an impact on all fields, especially in the education sector, which causes learning activities to be carried out online. The number of technology and information activists is currently gives rise to several educational support platforms. One of them is utilizing Google Sites as an online learning medium to increase student interest in learning. This study discusses the implementation of online learning using Google Sites media in increasing student interest in learning in Islamic Education Class 6 at SDN Ngringin, Moyudan, Yogyakarta. This research uses a descriptive qualitative approach. Collecting data through observation, interviews, and interviews. Test the validity of the data used is the source triangulation technique. The data analysis technique used is Miles and Huberman's qualitative which includes: data reduction, presentation, and making conclusions. The results of this study indicate that learning is carried out by the teacher pinning the Google Sites link in the description on the WhatsApp group followed by students studying and working on quizzes. The impact of this learning can increase students' interest in learning during the courageous period, this is indicated by the feeling of pleasure in students because of the ease of use, so students do not feel burdened during learning. Having pictures on Google Sites makes students feel interested in learning. Students focus more on learning because there are no other activities. Students are also actively involved in reading material, watching videos, and taking quizzes.